2020
DOI: 10.1007/s10683-020-09686-4
|View full text |Cite
|
Sign up to set email alerts
|

In absence of money: a field experiment on volunteer work motivation

Abstract: Although volunteers are a critical resource for non-profit organizations, little is known about how best to motivate them to work. A non-profit organization asked episodic volunteers to produce handmade greeting cards to sell at a fundraising event. By running a natural field experiment, we study the effect of motivating these volunteers through (a) the opportunity to vote on how the money that was raised would be spent and (b) the prospect of individual performance feedback. We find an economically and statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…The focus of value co-creation research is on the means to motivate consumers' value co-creation behavior. Monetary incentives have received the most academic attention (Mertins and Walter, 2021). Previous research revealed that more monetary incentives provided to consumers' value creation facilitate 10.3389/fpsyg.2022.1110011 Frontiers in Psychology 03 frontiersin.org more content creation (Sun et al, 2017).…”
Section: Literature Review and Research Hypotheses Value Co-creation ...mentioning
confidence: 99%
“…The focus of value co-creation research is on the means to motivate consumers' value co-creation behavior. Monetary incentives have received the most academic attention (Mertins and Walter, 2021). Previous research revealed that more monetary incentives provided to consumers' value creation facilitate 10.3389/fpsyg.2022.1110011 Frontiers in Psychology 03 frontiersin.org more content creation (Sun et al, 2017).…”
Section: Literature Review and Research Hypotheses Value Co-creation ...mentioning
confidence: 99%
“…Regarding volunteer staff, even though to be a volunteer is to participate willingly in the life of the association without financial compensation, volunteers usually contribute to the greater good as long as they feel they are making a meaningful contribution [46]. However, in a context where there is an insufficiency in human resources, motivate volunteer staff could help to retain them and ensure the continuity of care.…”
Section: Proposed Solutions To Improve Kmc Implementationmentioning
confidence: 99%
“…Indeed, a study showed that giving small money to volunteers did not help and impacted negatively their work. On the other hand, when volunteers in the same experiment were offered larger monetary rewards, the hours they offered to work were high; showing that in the absence of budget constraints, money may help to motivate volunteer staff [46,47]. Another study indicated that a volunteer program could meet needs and be a motivational force for both individual volunteer and the organization.…”
Section: Proposed Solutions To Improve Kmc Implementationmentioning
confidence: 99%
“…Overall, we found that very few studies focus on episodic volunteers (EVs) who help with fundraising. Among the existing studies, most focused on fundraising by EVs in one specific event or one type of event such as cancer related fundraising (Dunn et al, 2016), alumni fundraising (Khatri & Raheja, 2018), political fundraising (Gleicher, 2011), dance marathons (Masterson, 2016), charity sport events (Wood et al, 2010), and sale of hand-made cards in a charity event (Mertins & Walter, 2021). Among the exceptions is Boezeman and Ellemers (2007) who notably found that pride and respect among fundraising volunteers was associated with willingness to continue helping their respective charities.…”
Section: Introductionmentioning
confidence: 99%